Does Digital Nerve Injury Affect Range of Motion Recovery After Zone 2 Flexor Tendon Repair?. (March 2023) - Keane, Grace; Stonner, Macyn; Pet, Mitchell A.
Background: Evidence surrounding the impact of concomitant digital nerve injury on the outcome of zone 2 flexor tendon repair is sparse and conflicting. The purpose of this study is to assess the impact of digital nerve injury on the range of motion recovery after zone 2 flexor tendon repair. We hypothesized that digital nerve injury is independently associated with decreased motion after zone 2 flexor digitorum profundus (FDP) repair. Methods: This is a single-institution, multisurgeon retrospective analysis of patients treated with primary zone 2 FDP repair. Patients with or without digital nerve injuries were included. Patients with fracture, extensor tendon injury, dysvascularity, follow-up duration of less than 10 weeks, and younger than 15 years were excluded. The primary outcome measure was Strickland percentage at the last therapy visit. Bivariate analysis was performed using simple linear regression. These results were used to guide backward stepwise multivariable analysis of qualifying exploratory variables. Results: Forty-one patients with a total of 54 zone 2 FDP injuries qualified. Mean follow-up duration was 24 ± 10 weeks, and mean age was 38 ± 18 years. Thirty-three digits had a concomitant digital nerve injury, 26 digits had multidigit involvement, and 42 digits had combined FDP and flexor digitorum superficialis (FDS) injuries. Both older age and concomitant FDS injury exhibited independent relationships with poorer range of motion outcomes ( P < .05). Digital nerve injury, follow-up duration, gender, and multidigit involvement did not influence final digital motion. Conclusions: In patients undergoing zone 2 FDP repair, concomitant digital nerve injury is not independently associated with poorer postoperative active range of motion.